Hydatid Disease of Spine: A Rare Cause of Chronic Back-Ache Not Responding to Conventional Treatment - SAHU, ALOK; SENAPATI, RAJESH; HEMBRAM, GOPAL KRISHNA; SAHOO, MANOJ (International Journal of Innovative Research in Medical Science, 2024)
Hydatid disease is a parasitic infection caused by tapeworms in human. In human, it is common in liver, spleen and brain. Musculoskeletal involvement is secondary and uncommon, with an incidence of less than 2.5%. Spinal involvement is even rarer with an incidence of 1%. We came across an Afghan national in his early 20s who presented to us with the complains of gradually worsening pain in the upper back for 1.5 years associated with weakness of both lower limbs for 3 months. Within 2 weeks of presentation the neurological deficit progressed to complete paraplegia with loss of sensation below the level of the chest and urine retention. The patient was thoroughly examined clinically. Essential radiological and hematological investigations were performed as well. And a consequent diagnosis of hydatid disease of spine involving the chest wall was made. He was then operated by a multidisciplinary team consisting of cardiothoracic surgeon, orthopedic surgeons and anaesthetists. The cysts from the chest wall and the spine were excised followed by decompression of spine. Lavage with hypertonic saline was done intra-operatively to prevent recurrence. The post-operative period was uneventful and patient showed signs of improvement gradually. He was discharged and prescribed Albendazole and Praziquantel. Patient remained symptom-free for around one year. After a period of one year, signs of recurrence developed. Patient presented to us with paraplegia and had to be re-operated and put on similar post-operative drug regime of albendazole and praziquantel.